2017
DOI: 10.1080/15568318.2017.1340528
|View full text |Cite
|
Sign up to set email alerts
|

The equity impacts of bus rapid transit: A review of the evidence and implications for sustainable transport

Abstract: The paper offers an analysis of empirical evidence on the equity impacts of operational Bus Rapid Transit (BRT) systems in the Global South. The focus is on vertical equity, i.e. whether BRT systems achieve progressive benefits for poorer segments of the population. Findings from Africa, Asia and Latin America all suggest that BRT does offer significant benefits to lowincome groups, in terms of travel time and cost savings, access enhancement, and safety and health benefits. However benefits are often skewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 72 publications
2
62
0
Order By: Relevance
“…For instance, equity impact assessments could be required as part of permitting processes during rebuilding. Urban planners have used these assessments when planning for issues related to climate change, regional land-use planning, transportation, and road construction [85,106,107]. The assessments can be done at a micro-level (examining the impacts of specific policies or programs) or at a macro-level (assessing the mix of policies and programs) [108,109].…”
Section: Formal Mechanisms For Assessing and Addressing Inequitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, equity impact assessments could be required as part of permitting processes during rebuilding. Urban planners have used these assessments when planning for issues related to climate change, regional land-use planning, transportation, and road construction [85,106,107]. The assessments can be done at a micro-level (examining the impacts of specific policies or programs) or at a macro-level (assessing the mix of policies and programs) [108,109].…”
Section: Formal Mechanisms For Assessing and Addressing Inequitiesmentioning
confidence: 99%
“…Assessing equity impacts aids the development of recommendations on how to mitigate any negative impacts and maximize positive impacts and how to improve programs or services to be more responsive to specific populations. Case studies have shown that equity impact assessments can change decisions, enhance plan content, and improve plan implementation [106,110]. However, the assessment must be conducted in a timely manner prior to a plan's completion and have a clear definition of the scope, purpose, underpinning values, and what is hoped to be learned [111].…”
Section: Formal Mechanisms For Assessing and Addressing Inequitiesmentioning
confidence: 99%
“…Other principles include the ideas of formal equality, which requires that individuals who are alike in a relevant manner and belong to the same social group should be treated equally, and the principle of substantive equality, according to which people from different groups can be treated differently in order to promote equality of opportunities or outcomes. These principles of formal and substantive equality are often referred to as the principles of horizontal and vertical equity and have become the most common conceptual basis used in the transport equity literature in recent decades (Delbosc & Currie, 2011;Levinson, 2002;Litman, 2002;Manaugh & El-Geneidy, 2012;Sanchez et al, 2003;Venter et al, 2017).…”
Section: Nexus Of Justice and Transportationmentioning
confidence: 99%
“…Additionally, BRT requires a specific urban density profile to be financially viable that many Global South, and in particular, African cities lack [27]. Furthermore, whilst BRT has the potential to improve mobility for low-income users, evidence suggests that the benefits are skewed towards middle-income users [28,29]. From an environmental perspective, BRT is a road-based transport system that causes air pollution and emits greenhouse gases contributing to climate change (noting however that there are various pilot projects underway testing the viability of zero emission BRT bus systems).…”
Section: Introductionmentioning
confidence: 99%